Theory, algorithm and condition for aggregating economic benefit and health damages of coal fuelcombustion - Matsuki, Y.; Bidyuk, P.I. (Системні дослідження та інформаційні технології, 2013)
The purpose of the research is to test a possibility of using the theory of utility function in economics theory [1] for aggregating different kinds of variables such as economic benefit and ecological damages of industrial activities. An example of coal fuel combustion for electricity generation [2, 3] is selected for this test, which produces both economic benefit and human health damages. Several mathematical models for the utility function are tested with the data of the volume of combustions and the amount of air pollutions of twenty seven Oblasts of Ukraine by the regression analysis [4]. Consistent results are obtained upon the theory and the statistical data analysis. It is concluded that the prices take important role to give the weighting factor through the aggregation process of various indicators (independent variables) because in this theory the prices make up the total budget, which gives the constraints for maximizing the utility with given values such as number and volume of the indicators. Метою дослідження є перевірка можливості застосування в економічній теорії концепції функції корисності для агрегування різних змінних, таких як економічна вигода та екологічна шкода промислової діяльності. Для цієї перевірки обрано приклад спалювання вугільного палива для вироблення електроенергії, яке є джерелом як економічної вигоди, так і шкоди здоров’ю людини. За допомогою регресійного аналізу на підставі даних обсягу спалюваного матеріалу та рівня забрудненості повітря двадцяти семи областей проведено тестування декількох математичних моделей функції корисності. Отримані результати узгоджуються з теорією та аналізом статистичних даних. Автори дійшли висновку, що у процесі агрегування різноманітних індикаторів (незалежних змінних) важливе значення для коефіцієнта зважування мають ціни, оскільки у цій теорії вони визначають загальний бюджет, який встановлює обмеження для максимізації корисності за цих параметрів, таких як кількість та величина індикаторів. Целью исследования является проверка возможности применения в экономической теории концепции функции полезности для агрегирования разных переменных, таких как экономическая выгода и экологический вред промышленной деятельности. Для данной проверки выбран пример сжигания угольного топлива для выработки электроэнергии, являющегося источником как экономической выгоды, так и вреда здоровью человека. С помощью регрессионного анализа на основании данных объема сжигаемого материала и уровня загрязненности воздуха двадцати семи областей проведено тестирование нескольких математических моделей функции полезности. Полученные результаты согласуются с теорией и анализом статистических данных. Авторы пришли к выводу, что в процессе агрегирования различных индикаторов (независимых переменных) большое значение для коэффициента взвешивания имеют цены, поскольку в этой теории они определяют общий бюджет, устанавливающий ограничения для максимизации полезности при данных параметрах, таких как количество и величина индикаторов.